Editorial: Globalization Toward Locality - Editor Al-Jami'ah: Journal of Islamic Studies (Al-Jami'ah: Journal of Islamic Studies, 2005)
Seemingly, Globalization, the recent world phenomenon, will get rid of all frontiers possessed by a state. This is due to the fact that each person, whatever citizenship the person possesses, may communicate with any one else wherever he or she live, and may move to any place to which he or she would like. Accordingly, the world phenomenon will play great roles in setting particularly socio-cultural, political, educational, and legal patterns and formulations of locality. However, this locality is an exception. It is a distinctive and peculiar border. The Great Tradition, possessed by the Reflective Few, is going to be hand in hand with the Little Tradition of the Unreflective Many to shield their local properties. They won’t let outsiders, through the globalization stream, destruct their local social structures, even though such consciousness belongs more greatly to the former group rather than the latter. However, the former is used to invite the latter to cooperate in handling foreign destructive influences.